A REVIEW OF EXTRATERRESTRIAL ORGANIC CARBON AND ITS POTENTIAL IMPACT OF LIFE ON EARTH - Firza Riyadhini Yarkasih; Tutut Nurita; Nariyah Al-Zahzamri; Riska Ayu Pratiwi (Cahaya Ilmu Bangsa Institute, 2024)
Meteorites bombarded the Earth's surface during the early days, early evolution and proliferation of life. It has the potential to provide a source of abiotic organic carbon to support early life. This study aims to analyze research methods used in detecting the use of space organic carbon, analyze research results related to the role of space organic carbon, and provide further understanding to researchers related to organic carbon from space and its potential role and use in human life on earth. This study uses a systematic review method using 15 selected sources from a total of 50 sources of information on national and international news and journal articles related to space organic carbon and its potential. The results of this study showed that extraterrestrial organic carbon produces a source of carbon that is beneficial for microorganisms to integrate into their proteins. By combining inverse stable isotope labeling and infrared spectroscopy, this study shows that organic carbon from Aguas Zarcas carbon chondrite can be harnessed for cell growth. Previous discoveries have also shown that aerobic microbial communities have the potential to be in future human space settlement plans to metabolically access and research carbonaceous asteroid material.